2009
DOI: 10.1107/s0907444909040153
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Taz2 domain of p300: insights into ligand binding

Abstract: CBP and its paralog p300 are histone acetyl transferases that regulate gene expression by interacting with multiple transcription factors via specialized domains. The structure of a segment of human p300 protein (residues 1723-1836) corresponding to the extended zinc-binding Taz2 domain has been investigated. The crystal structure was solved by the SAD approach utilizing the anomalous diffraction signal of the bound Zn ions. The structure comprises an atypical helical bundle stabilized by three Zn ions and clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…This unusually long helix makes no contacts with the rest of the TAZ domain but engages in extensive interactions with symmetry related molecules in crystal (70). It was not observed in the NMR structure of the same domain bound to p53 because a shorter p300 fragment (1723–1812) was used (14).…”
Section: Discussionmentioning
confidence: 99%
“…This unusually long helix makes no contacts with the rest of the TAZ domain but engages in extensive interactions with symmetry related molecules in crystal (70). It was not observed in the NMR structure of the same domain bound to p53 because a shorter p300 fragment (1723–1812) was used (14).…”
Section: Discussionmentioning
confidence: 99%
“…The promiscuity of this binding site has resulted in some potentially misleading interactions in x-ray structures. In the crystal structure of free TAZ2, a C-terminal extension of the ␣ 4 helix extends beyond the globular core and docks to the hydrophobic surface on a neighboring molecule in the crystal lattice, mimicking the interactions of TAZ2 with the amphipathic helices of regulatory IDRs (33). The long ␣ 4 helix observed in the x-ray structure appears to be stabilized by lattice contacts.…”
Section: Taz2 Interactionsmentioning
confidence: 99%
“…Structural studies have revealed that TAZ2 forms a four a-helix core structure linked by three short loops that comprise zinc binding motifs [14,22] and those of TAZ2 in complex with p53, Stat1 and E1a reveal that a-helical TAD segments dock against different surfaces of the TAZ2 a-helical core with different binding modes [14][15][16][17]. Since our studies raise the possibility that GR helical segments could be responsible for binding to the TAZ2 (Fig.…”
Section: Multiple Gr Tau1c Peptides Bind To Cbp Taz2mentioning
confidence: 80%